Vacuum Cleaner Robot with Arduino R3 Android Based - D. Desmulyati; Hafdiarsya Saiyar; Martua Hami Siregar; Mohammad Noviansyah (Manunggal Halim Jaya, 2024)
The advancement of science and robotics technology has made human life faster and easier. The field of robotics now encompasses all sectors, including industry, mechanics, and household. Therefore, a floor vacuum robot is needed to facilitate home cleaning. This research discusses a vacuum robot that uses Arduino Uno, ultrasonic sensors, and Bluetooth serial to operate the robot. This vacuum robot moves automatically using ultrasonic sensors that move forward while avoiding obstacles such as walls, which act as distance detectors. This allows the robot to automatically turn and avoid obstacles, continuing the cleaning process. Meanwhile, the Bluetooth system can also be manually controlled via a smartphone, allowing it to move forward, backward, turn, and stop. With a DC motor, you can manually operate the vacuum cleaner by pressing the on/off button located on the body of the robot. This robot makes household chores easier to accomplish.